THE RESULT OF PLANT PATHOGENIC FUSARIUM SPP ISOLATED FROM CONIFEROUS FOREST IN NEAR ULAANBATAAR CITY - Nasanjargal, D; Otgonzaya, M; Chinzorig, R; Byambasuren, M (Mongolian Journal of Agricultural Sciences, 2015)
Fusarium type of fungi forms whitish or bright color and grows really fast. Fusarium subglutinans f. sp. pini (F. circinatum Nirenbery & O’Donnell), F. Oxysporum f. sp. Psidii and F. solani are widely distributed plant entomopathogenic fungi. This fungus usually gives a signs of yellowing, drying and shedding when causing disease. Main aim of our study is to identify Fusarium spp fungi based on disease symptoms such as yellowing, drying and shedding of the needles then define isolated pure culture of fungi and formulate control method. [4,6,7] In this study atotal of sixty-nine samples including larch, pine and spruce were collected from 8 locations out of 127 pieces collected from 13 locations are used. According to standard methodology, when isolating mixed and pure culture samples were placed on wet Petri dish in incubator at 26°C for 7 days until the fungus growth appearedalso average mycelia growth and conidia have observed. This Fusariumspecie typically gives whitish tinged grayish-violent color in colony center on PDA. Observing culture mycelia growth and conidia, genus name has identified using “Identification of Mitosporic Fungi” by Dr. Katsuhiko Ando. When formulating control method against fungi, bioproduct of Bacillus subtilis 26D strain, made in Russian as well as plant originated bioproduct called 1.5 % Matrine & Osthole Asmade in China have been experimented against entomopathogenic fungi Fusarium sppareused. Based on the study results Fusarium type of fungi is detected from samples taken from Bogdiin am, Jigjid and Taivan mountain. Hence bioproduct of Bacillus subtilis 26D strain inhibited fungal growth whereas can be possible biocontrol for Fusarium spp whereas plant originated bioproduct 1.5% Matrine & Osthole AS made in P.R.C cannot inhibit the growth of this fungi. Forest morbidity is not well researched in Mongolia. Based on our research forest regions near Ulaanbaatar city have higher morbidity rate. Disease symptoms of conifers have shown yellowing, drying and even shedding of the needles. A total of sixty-nine samples including larch, pine and spruce were collected from 8 locations near Ulaanbaatar city. Samples were placed on wet plates in incubator at 26°C for 7 days until the fungus growth appeared. Fresh fungal growth from the plated samples then transferred onto PDA. Fusarium species typically have average mycelia growth, aerial mycelium and gives whitish tinged grayish-violent color in colony center on PDA. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 101-104